Evaluasi User Experience pada Prototipe Website Wedding Organizer Menggunakan Metode UEQ pada Lenny Wedding Gallery Palembang - Risang Narota Ragwedha; Nur Widjiyati (Applied Information Technology and Computer Science (AICOMS), 2026)
Lenny Wedding Gallery Palembang is a wedding organizer service provider that still uses social media for promotion and ordering services. This condition causes limitations in the presentation of information and interaction between service providers and customers. This study aims to assess the quality of user experience on the prototype website of the wedding organizer Lenny Wedding Gallery Palembang by applying the User Experience Questionnaire (UEQ) method. The website is designed as a digital promotion tool as well as a service ordering medium to improve the quality of interaction between the system and users. The evaluation was conducted on 31 user respondents who had tried the website prototype. UEQ is used to measure six dimensions of user experience, including attractiveness, perspicacity, efficiency, dependability, stimulation, and novelty. The evaluation results show that all UEQ dimensions obtained an average value above the positive limit (>1.8) with the Excellent category. This indicates that the website prototype has a high level of ease of use, clarity of information, interaction efficiency, and visual appeal, making it worthy of being developed into a comprehensive system implementation stage.